Altered expression of TIM‐3, LAG‐3, IDO, PD‐L1, and CTLA‐4 during nimotuzumab therapy correlates with responses and prognosis of oral squamous cell carcinoma patients. (9th June 2019) - Wang, Hong; Mao, Lu; Zhang, Tian; Zhang, Liming; Wu, Yuteng; Guo, Wei; Hu, Jingzhou; Ju, Houyu; Ren, Guoxin
Abstract: Background: Since the inhibitory immune checkpoint receptors have been described to benefit the OSCC patients clinically, it is unknown that whether their expression in tumor immune microenvironment (TME) can determine the clinical outcome in response to nimotuzumab therapy. Methods: We examined the expression patterns of immune checkpoint receptors (including TIM‐3, LAG‐3, PD‐L1, and CTLA‐4) and an immunoregulatory enzyme called IDO in 36 OSCC patients during nimotuzumab therapy by immunohistochemistry. Then, we divided the recruited patients into clinical responders and non‐responders according to computed tomography (CT) scan and analyzed the relationship between the immunological parameters and clinical outcome. Results: We observed that nimotuzumab therapy significantly increased the expression of TIM‐3, LAG‐3, IDO, PD‐L1, and CTLA‐4 in the TME, and the expression of LAG‐3 and PD‐L1 before nimotuzumab therapy was inversely correlated with the overall survival. In clinical non‐responders, we found the expression of TIM‐3, LAG‐3, IDO, PD‐L1, and CTLA‐4 was significantly increased during nimotuzumab therapy, and the expression of TIM‐3, LAG‐3, IDO, PD‐L1, and CTLA‐4 before nimotuzumab therapy was negatively correlated with the overall survival. However, in clinical responders, neither of those showed significant. Conclusions: It suggests that these immune checkpoint receptors and IDO could be considered as biomarkers to reflect immune status in the tumor microenvironment during nimotuzumab therapy. Blockade of these immune checkpoint receptors might enhance nimotuzumab‐based cancer immunotherapy, thus potentially improving clinical outcomes of OSCC patients.